Online Behavioural Advertising and the Protection of Children’s Personal Data on the Internet - Jaroszek, Agata (University of Wroclaw. Faculty of Law, Administration & Economics, 2014)
The paper discusses problems emanating from the current and planned legal framework of the European data protection of children that have emerged and have to be addressed, particularly with regard to the social impact that information and communication technologies have on the way children communicate and make choices online. Given that such problems are not only confined to European countries, approaches to regulating children’s privacy on the internet from outside the EU are also discussed where relevant.While in Europe privacy is protected as one as the fundamental human rights that deserves legal safeguards enshrined in the volume of laws that establish comprehensive sets of right and responsibilities for states and individuals, in the United States personal data are perceived primarily as a commercial commodity, thus resulting in the adaptation of a diverse and targeted approach based on the Fair Information Practices Act (FIPA model of data privacy protection). However, it is inevitable that both approaches need to establish long-term policies for the protection of minors (children) and more vulnerable members of societies on the Internet, in particular in the area of online behavioural advertising and other marketing techniques that aim at profiling of individuals.
Keywords: reklama behawioralna online; ochrona danych osobowych dzieci; internet